Chitin synthesis in the salmon louse Lepeophtheirus salmonis - Hardardottir, Hulda Maria (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology, 2021)
The salmon louse Lepeophtheirus salmonis is a parasitic copepod that lives and feeds on Atlantic salmon (Salmo salmar). At present, this parasite is the number one threat to the Norwegian aquaculture. The density of salmons living together in aquaculture sea cages gives the salmon lice optimal conditions for infecting and reproducing. Many delousing methods, both non-chemical and chemical, are available for the treatments of salmon lice. In salmon aquaculture, four benzoylureas-derived chitin synthesis inhibitors (CSI) are used: Hexaflumuron, diflubenzuron, teflubenzuron, and lufenuron. In-feed treatments based on diflubenzuron or teflubenzuron are used by Norwegian farmers, while hexaflumuron- and lufenuron-based treatments are known to be available in Chile. Despite many options for treating lice, current treatments are not optimal because 1) resistance can develop, 2) there are environmental issues associated with chemical treatments, and 2) non-chemical treatments can inflict stress-related damage on the fish. Therefore, new treatments are needed. By investigating the molecular biology of L. salmonis, it is hoped that new candidates can be discovered. Salmon lice have a rigid exoskeleton around the body, which must be removed for future growth to occur. During the development, the salmon louse molt to get to the next life stage. Molt, or ecdysis, is an essential process in all arthropods, and the salmon louse molts eight times to reach the adult life stage. Chitin is one of the main components of the exoskeleton, and the chitin synthesis pathway is very conserved in chitin-synthesizing organisms. The key chitin synthesis transcripts (LsGFAT, LsGNA1, LsAGM, LsUAP, and LsCHS1/2) were cloned and their sequences were analyzed to understand chitin synthesis in L. salmonis better. The results showed that L. salmonis has enzymes similar to other arthropods and these are most similar to other crustaceans' sequences, especially other copepods. The expression patterns of these chitin synthesis genes and chitinases ...